ANALISIS EKONOMI ISLAM TERHADAP PEMUNGUTAN PAJAK PENGHASILAN (Pph 21) - AGUSTIN MILA ARLINA; MUSTOFA MUSTOFA; AHMAD AGUS HIDAYAT (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2023)
Income tax (PPh 21) is a mandatory payment, related to the gain that a person receives from a person's work, service, or activity. Income tax is collected based on a progressive levy rate that adjusts the amount of the taxpayer's income, the greater the income, the greater the percentage of levy imposed. In this study, it shows that the determination of progressive income tax rates (PPh 21) is obtained from the perspective of equality and benefit, and income tax (PPh 21) achieves 3 out of 4 tax accumulation principles (dharibah) in the Islamic economy as a result of which income tax is taken from the obligatory tax allowed.